Self-independence of oncological geriatric patients in the home environment - Miroslava, Bednáriková; Réka, Zöldi; Lubica, Libová (Magyar Gerontológia, 2023)
Cancer is one of the most dreaded diseases in the world. Family plays an important role in managing this disease. It provides home care for the patient, helps to increase and maintain the patient's self-sufficiency. A number of factors influence the patient's self-sufficiency, such as the age of the patient, the type of illness, the method of treatment, the patient's psychological state, the environment in which the patient is located, etc. Self-sufficiency in patients contributes to their self-esteem and to a positive perception of themselves.